A Polyaromatic Gemini Amphiphile That Assembles into a Well‐Defined Aromatic Micelle with Higher Stability and Host Functions. Issue 20 (4th April 2019) - Nishioka, Tomoya; Kuroda, Kiyonori; Akita, Munetaka; Yoshizawa, Michito
Abstract: A gemini‐type amphiphilic molecule, constituted of two V‐shaped polyaromatic amphiphiles linked by a linear acetylene spacer, was synthesized. The gemini amphiphile assembles into a well‐defined aromatic micelle (ca. 2 nm in core diameter), providing higher stability in water even at low concentration (0.09 mm ) and high temperature (>130 °C). Unlike common gemini amphiphiles with aliphatic chains, the present amphiphile and its micellar assembly emit green and orange fluorescence ( Φ F =33 and 9 %), respectively. Despite strong and multiple π‐stacks of the polyaromatic panels of the amphiphiles, the water‐soluble gemini aromatic micelle incorporates medium‐size to large hydrophobic compounds into the frameworks. Interestingly, the guest binding capability toward large planar molecules was enhanced by more than two times through the pre‐encapsulation of spherical molecules in the cavity. Abstract : A gemini‐type polyaromatic amphiphilic molecule assembles into a well‐defined aromatic micelle with higher stability in water. The gemini micelle incorporates medium to large hydrophobic compounds into the frameworks. The guest binding capability toward large planar molecules is significantly enhanced through the pre‐encapsulation of spherical molecules in the cavity.